Ampicillin‐ and ampicillin/sulbactam‐resistant Escherichia coli infection in a neonatal intensive care unit in Japan. Issue 6 (June 2016) - Saida, Ken; Ito, Yukako; Shima, Yosuke; Kasuga, Eriko; Kusakari, Mai; Miyosawa, Yukihide; Baba, Atsushi
Abstract: The incidence of ampicillin (ABPC)‐resistant Escherichia coli ( E . coli ) infection in very low‐birthweight infants has been increasing. The rate of ABPC/sulbactam (ABPC/SBT)‐resistant E . coli in this population, however, is currently unknown. We encountered two cases of severe infection due to resistant E. coli and retrospectively studied the prevalence of ABPC‐ and ABPC/SBT‐resistant E . coli in regular surveillance cultures obtained from all neonatal intensive care unit (NICU) patients between 2000 and 2013. The overall prevalence of ABPC‐resistant E . coli was 39% (47/120), accounting for 63% of cases (32/51) between 2007 and 2013, compared with 22% (15/69) between 2000 and 2006. The prevalence of ABPC/SBT resistance was 17% (20/120), which was similar in both periods (16%, 8/51 vs 17%, 12/69). According to these results, not only ABPC, but also ABPC/SBT‐resistant E . coli must be considered in the NICU.